2023
DOI: 10.1177/14680874231184279
|View full text |Cite
|
Sign up to set email alerts
|

Pre-ignition-prevention control method in spark-ignition engines by detecting precursory cycles with an ion-current sensor

Abstract: In gasoline engines with a higher compression ratio, abnormal combustion, such as pre-ignition and knocking, tends to occur due to higher temperature in the combustion chamber, which leads to lower engine performance. To prevent pre-ignition from occurring, we propose a pre-ignition-prevention control method that involves using an ion-current sensor integrated in an ignition system. The pre-ignition and precursory cycles are detected from the ion-current intensity and spark-discharge duration estimated from io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Ion current has been used to obtain flame information and detect misfires (41)(42)(43) , and studies have shown that it can be used to obtain the combustion state even for compression ignition at lean conditions in HCCI (44)(45)(46) engines. In addition, the detection of abnormal combustion, knocking and pre-ignition (47)(48)(49)(50)(51) , and the possibility of detecting precursors to preignition (52,53) have also been reported. Kumano et al (52) investigated the characteristics of ignition precursor phenomena in gasoline engines with a high compression ratio by using an ion current sensor integrated into the spark ignition coil.…”
Section: Combustion Control Of Advanced Enginesmentioning
confidence: 99%
“…Ion current has been used to obtain flame information and detect misfires (41)(42)(43) , and studies have shown that it can be used to obtain the combustion state even for compression ignition at lean conditions in HCCI (44)(45)(46) engines. In addition, the detection of abnormal combustion, knocking and pre-ignition (47)(48)(49)(50)(51) , and the possibility of detecting precursors to preignition (52,53) have also been reported. Kumano et al (52) investigated the characteristics of ignition precursor phenomena in gasoline engines with a high compression ratio by using an ion current sensor integrated into the spark ignition coil.…”
Section: Combustion Control Of Advanced Enginesmentioning
confidence: 99%